(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Kolaviron is a mixture of bi-flavonoids from seed Garcinia kola seed, and has been previously shown to exhibit Nrf2 antioxidant-mediated inhibition of neuroinflammation in LPS-activated BV2 microglia. In this study, we investigated neuroprotective effects of kolaviron in LPS-induced memory impairment in rats. Wistar rats (225–250) g was used for this study. Memory impairment was induced with the systematic administration of 250 µg/mg lipopolysaccharide (LPS). The effect of kolaviron on the cognition and learning processes were assessed using the behavioral responses in the Morris water maze model. Effects of LPS injections on the physiological activities were assessed by biochemical assays before and after treatment. Peripheral administration of LPS showed reduction in the cognitive and locomotor process. It also led to reductions in the core body temperature, superoxide dismutase (SOD), and catalase levels, with an increase in Membrane lipid-peroxidation (MDA), intracellular glutathione (GSH) and nitric oxide (NO2). These pro-inflammatory mediators produced in response to LPS are hypothesized to affect cognition, and kolaviron was able to ameliorate the effect by significantly improving the cognitive and learning processes, revealed in the reduction of escape latency and path-length during the probe trial and increase in time spent within the quadrant during retrieval using Morris water maze. Similarly, LPS at 250 µg/kg induced a hypothermic effect in the treated animals. Kolaviron significantly was able to ameliorate the level of SOD and CAT by causing a significant increase while it caused a significant reduction in the level of NO2, GSH, and MDA. Kolaviron has considerable anti-inflammatory potentials, reducing lipopolysaccharide activation of macrophages. The memory-enhancing activity of kolaviron was comparable to Sulindac sulfide (a non-steroidal anti-inflammatory drug).